1981
DOI: 10.1139/y81-025
|View full text |Cite
|
Sign up to set email alerts
|

Methylene blue inhibits coronary arterial relaxation and guanylate cyclase activation by nitroglycerin, sodium nitrite, and amyl nitrite

Abstract: Relaxation by nitroglycerin, sodium nitrite, and amyl nitrite of bovine coronary arterial smooth muscle was inhibited by the oxidant methylene blue. Methylene blue also inhibited activation of bovine coronary arterial soluble guanylate cyclase by nitroglycerin, which required addition of cysteine. At concentrations less than 10 mM, sodium nitrite required the addition of one of several thiols or ascorbate to activate guanylate cyclase from bovine coronary artery. Guanylate cyclase activation by large amounts (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
102
0

Year Published

1986
1986
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 316 publications
(106 citation statements)
references
References 0 publications
4
102
0
Order By: Relevance
“…Therefore it is suggested that NO is involved in the CPAinduced relaxation of rat arteries. Further evidence supporting this idea is that the NO pathway inhibitors, such as the NO synthase inhibitor, L-NOARG (Moore et al, 1990), the NO scavenger, haemoglobin (Gruetter et al, 1981) and the soluble guanylate cyclase inhibitor with cyclic GMP-lowering activity, LY83583 (Malta et al, 1988;MUlsch et al, 1988) each suppressed both the CPA-induced relaxation and cyclic GMP formation.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore it is suggested that NO is involved in the CPAinduced relaxation of rat arteries. Further evidence supporting this idea is that the NO pathway inhibitors, such as the NO synthase inhibitor, L-NOARG (Moore et al, 1990), the NO scavenger, haemoglobin (Gruetter et al, 1981) and the soluble guanylate cyclase inhibitor with cyclic GMP-lowering activity, LY83583 (Malta et al, 1988;MUlsch et al, 1988) each suppressed both the CPA-induced relaxation and cyclic GMP formation.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, inability of atropine to attenuate the relaxation by the nerve stimulation (Toda, 1975(Toda, , 1982a excludes the in volvement of a cholinergic mechanism. Relaxations induced by transmural electrical stimulation and nicotine were abolished by methylene blue, a gua nylate cyclase inhibitor (Gruetter et al, 1981). Therefore, the transmitter substance released from the vasodilator nerve may act on smooth muscle and activate guanylate cyclase, thus increasing cy-N. TODA clic GMP levels, and inhibitions of the relaxant re sponse by hemolysate may result from decreased cyclic GMP production.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrite has been shown to exhibit vasodilatating activity in vitro at high concentrations [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%